Tourism Development of Cultural Heritage Resources Through Conservation Concepts: A Case Study of Ningxia, China - Shengrui Zhang; Tianyi Hu; Tongyan Zhang; Hongrun Ju; Yingjie Wang (Land)
Cultural heritage resources represent a vital aspect of tourism in the Ningxia Hui Autonomous Region, an area characterized by its ethnic minority heritage. This study innovatively proposes a classification framework for cultural heritage based on the principles of protection and the demands of tourism development. For the first time, it combines kernel density analysis and spatial autocorrelation methods to conduct a quantitative study on the geographical distribution of cultural heritage in Ningxia, covering aspects such as scale, structure, distribution characteristics, and influencing factors. The findings reveal: (1) Religious and Ceremonial Sites: Ningxia boasts the highest number of religious and ceremonial sites, totaling 1741. (2) Geographical Distribution: Resources are distributed in a multicore pattern, concentrated in Longde and Zhongning Counties, while the central and western areas are less rich. (3) Regional Concentration: The eastern region shows a high concentration of resources, contrasting with the low concentration in the north. (4) Influencing Factors: Social factors like GDP per capita, urbanization, and population density significantly affect this spatial pattern, although natural factors like altitude are also important. Consequently, the paper recommends increased government investment in cultural heritage tourism; enhanced integration of heritage tourism between urban core areas and countryside zones; increased investment in the protection and development of cultural heritage in high-altitude and remote areas. These findings aim to promote the sustainable growth of Ningxia’s cultural heritage and offer insights for similar regions.